การพัฒนาอาหารสำหรับเพาะเลี้ยง Escherichia coli DH5 ในถังปฏิกรณ์ชีวภาพให้ได้เซลล์ที่มีความหนาแน่นสูง - สติปัฏฐาน อติกานต์; ปิยพิทยานันต์ ชนิตโชต; เจริญรัตน์ เทพปัญญา; สุขุมศิริชาติ วาสนา (Thai Journal of Science and Technology, 2021)
Escherichia coli expression system is a robust and cost-effective recombinant protein expression system. In order to maximize the productivity of this system, increasing the cultivation scale and cell density is necessary. However, several engineered E. coli strains, such as E. coli DH5a, are auxotrophic mutants therefore are unable to grow in the synthetic medium that is generally designed for high cell density cultivation. Thus, to achieve high cell density of the auxotrophic mutant strains of E. coli, the cultivation medium was newly developed by supplementing yeast extract and peptone to the Bylund’s synthetic medium, designated Bylund:LB medium. The results showed that E. coli DH5a was able to grow and reached OD600 of 17.70 in Bylund:LB medium with 1 g/L yeast extract and 2 g/L peptone using fed-batch process in a bioreactor. However, an increase in yeast extract to 2 g/L and peptone to 4 g/L did improve the OD600 to 53.10. It was obvious that the obtained cell density was directly correlated to an increase in yeast extract concentrations and peptone supplemented in Bylund:LB medium.